An investigation into the impact of implementation of the Rural Development Strategy in Muyexe Village in the Greater Giyani, Limpopo Province - Bila, Tsakani Ephraim (University of Limpopo (Turfloop Campus), 2013)
The study was conducted to examine the impact of the implementation of the comprehensive rural development programme, President Zuma referred to it as the integrated rural develooment in is presidential inaugural speech in 2009. The researcher went to Muyexe village to conduct the research as well as to observe what took place. The researcher interviewed community members as well as community leadership who indicated how the community has been transformed to what it was, which they described a squalor living condition to what it is today, a community that meets the most basic needs required for sustainable livelihood. The people of Muyexe owe their changed fortunes to the government’s Comprehensive Rural Development Programme developed and coordinated by the Department of Rural Development and Land Reform. Sector departments and other development agencies were mobilised to work together towards a common goal to improve the lives of rural people. The intervention brought numerous changes to the community of Muyexe village. The lives of the community has been improved, through the intervention the community now have access to health care, early child hood development centre, community multi community centre, and so forth. The community spoke fondly of the reduction in crime and the killings of their cattle by wild animals; the reduction is caused by the establishment of the police station and the fencing around of the village. Despite what had been achieved by the intervention, Government should regard what happened as an initial intervention to focus on meeting people’s basic needs, especially food security. The next step should be the entrepreneurial stage and large scale infrastructure development.
Thesis (M.Dev.) --University of Limpopo, 2013
Keywords: Rural development programme; Rural community leadership; 307.1412; Rural Development -- South Africa -- Limpopo Province; Rural Development Projects -- South Africa -- Limpopo Province